2006
DOI: 10.1590/s0004-282x2006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the cerebrospinal fluid laboratory parameters in the ELISA test for neurocysticercosis using a total cysticerci antigen

Abstract: -To evaluate if the cere b rospinal fluid (CSF) parameters may influence the cysticercosis immunoreactivity response in the CSF. CSF samples of 109 patients were analyzed and classified in three gro u p s , a c c o rding to the neurological manifestations and the reactivity in antibody-enzyme linked immunosorbent assay (Ab-ELISA) testing in CSF for neuro c y s t i c e rcosis (NC): group A, 18 patients with neurological diso rders compatible with NC and reactive Ab-ELISA in CSF for NC; group B, 50 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Several studies have shown that the performance of the ELISA method for diagnosis of neurocysticercosis is better in the stages of cysticercus degeneration [18][19][20] . These results are different from the present study, where six of the 15 patients with negative ELISA presented cysts in degeneration, while only one of the seven patients with positive ELISA presented cysts in degeneration.…”
Section: Carvalho-junior Rm Et Al -Enzyme Immunoassay For Diagnosis Omentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the performance of the ELISA method for diagnosis of neurocysticercosis is better in the stages of cysticercus degeneration [18][19][20] . These results are different from the present study, where six of the 15 patients with negative ELISA presented cysts in degeneration, while only one of the seven patients with positive ELISA presented cysts in degeneration.…”
Section: Carvalho-junior Rm Et Al -Enzyme Immunoassay For Diagnosis Omentioning
confidence: 99%
“…Reviewing the literature, it appears that the ELISA method has shown different sensitivity and specificity scores [17][18][19][20][21][22][23][24][25][26][27][28] . This study determined a sensitivity of 31.8% and specificity of 100% for the ELISA method in CSF in relation to diagnosing neurocysticercosis, which implies low sensitivity of ELISA for diagnosing neurocysticercosis, with a 68.3% rate of false negative.…”
Section: Carvalho-junior Rm Et Al -Enzyme Immunoassay For Diagnosis Omentioning
confidence: 99%